Training and Mentoring on the Use of Kahoot to Increase Student Engagement and Motivation at SMAN 1 Kefamenanu - Jonris Tampubolon; Desta Gloria Siahaan; Fitra Ramadhan; Lukas Pardosi (JURNAL ABDIMAS MADUMA, 2026)
This Community Service Activity aims to increase the engagement and motivation of students at SMAN 1 Kefamenanu through training and mentoring using Kahoot as an interactive gamification-based learning medium. The activity was carried out in three main stages: training, mentoring, and evaluation, involving 50 teachers and 50 students. The training focused on improving teachers' abilities in designing and managing Kahoot quizzes, while mentoring was provided to ensure that teachers could implement the use of Kahoot in the classroom learning process. Evaluation was carried out through observation, questionnaires, interviews, and analysis of quiz results to obtain quantitative data. The results of the activity showed a very high level of participant enthusiasm with an attendance rate of 97%. 93% of teachers were able to create and manage quizzes well and 86% were able to implement them in the classroom learning process. From a student perspective, 95% said Kahoot could increase their engagement in learning and 96% experienced increased learning motivation and 82% were able to answer quiz questions correctly. The level of participant satisfaction reached 85% and 78% of teachers expressed a commitment to using Kahoot continuously. Based on these results, it can be concluded that training and mentoring on the use of Kahoot are effective in improving teacher competence, student engagement, and learning quality, and have good potential for sustainability if supported by continued mentoring and school policies that support the use of learning technology.Keyowords: Student Engagement, Motivation, Kahoot, Gamification, Training, Mentoring